Decision Support Systems in Health Care - Walus, Y. E.; Ittmann, H. W.; Hanmer, L. (Methods of Information in Medicine, 1997)
This paper delineates the application of decision support systems in the healthcare arena. An overview of decision support systems in the healthcare environment in the last three to five years, mostly in the USA and the UK is provided. Some reference is made to work in South Africa. Although this report endeavours to emphasise the decision support system side, some operations research issues are also addressed. This paper is divided into several sections: decision support systems definition, techniques used, the use of operations research in specific areas of healthcare, information systems, assessment of decision support systems, in-house development, decision support in South Africa and future of decision support systems.
Keywords: Decision Support Systems; Healthcare; Case Studies